Pubertal trajectory in females with Rett syndrome: A population-based study - Knight, O.; Bebbington, A.; Siafarikas, A.; Woodhead, H.; Girdler, Sonya; Leonard, H. (Elsevier, 2013)
Background: Rett syndrome is a severe genetic neurodevelopmental disorder mainly affecting females. The aim of this study was to describe pubertal development in a population-based cohort of females with Rett syndrome. Methods: To assess pubertal trajectory we used six waves of data provided by parents of girls and women, recruited through the Australian population-based Rett Syndrome Database. The age at which adrenarche, thelarche or menarche occurred was used as the parameter for time to event (survival) analysis. The relationships between BMI, mutation type and the trajectories were investigated, using Cox proportional hazards. Results: One quarter of girls reached adrenarche by 9.6 years, half by 11 years and three quarters by 12.6 years. Half reached menarche by 14 years (range 8–23). Being underweight was associated with later age at adrenarche, thelarche and menarche, while higher BMI (overweight) was associated with earlier onset. In general, girls with C-terminal deletions and early truncating mutations reached pubertal stages earlier and those with the p.R168X mutation reached them later. Conclusion: The pubertal course in Rett syndrome may be abnormal, sometimes with early adrenarche but delayed menarche. These features may be genotype dependent and may have varying relationships with growth and bone acquisition.